USE OF GREEN COCONUT MESOCARP IN THE PRODUCTION OF LETTUCE - Silva, Alessandro Costa da; França, Nirany Reis (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The objective of this work was to evaluate the green coconut mesocarp in production of lettuce. This research was carried out in Mojó village, in Paço de Lumiar County, MA. The experiment was completely randomized, with six treatments and four replications, and each experimental unit was constituted by 36 plants. All treatments with green coconut mesocarp developed better than the control plant. It is concluded that the use of green coconut mesocarp with manure of chicken improve the physical soil quality, increasing the production of lettuce.